Desenvolvimento e avaliação do aplicativo “autismo-cartões de emoções, expressões e ações” - TRAVASSOS, Talita de Cacia Sousa (2019)
Autism Spectrum Disorder (ASD) is a behavioral syndrome that affects children's development. The TEA usually manifests itself in the first two years of the child's life, and is currently classified into three levels, ranging from mild, moderate to severe. According to recent studies, the distinction between levels occurs taking into account the degree of impairment in the reciprocal communication and in the social interaction of the child. It is important that the follow-up of children diagnosed with ASD by specialized professionals should start as early as possible so that it receives the necessary help and develops in the best way possible. The technology is considered by experts as a good ally in the monitoring and development of people with ASD. With the use of technology it is possible to create interesting and non-distracting environments, so it is easier to follow difficulties and advances, and thus create the best strategies for the best development of the individual. Taking this into account, the application and game "Autism - Action and Emotion Cards (CEEA)" was developed, which seeks to be an aid tool for professionals and responsible for children with ASD. After the development, tests and evaluations were carried out with specialists to evaluate the application. 22 participants participated in the assessments, of which 100% agree that the application is a useful tool in the development of children with ASD.